2023
DOI: 10.24349/1icc-70f3
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on the validity of the genus Abalakeus (Acari: Erythraeidae) with a redescription of A. gonabadensis

Abstract: The validity of the genus Abalakeus is discussed and redefinitions are provided for the genera of Abalakeus and Eatoniana. Abalakeus gonabadensis is redescribed from type specimens and larvae ectoparasitic on different grasshoppers (Orthoptera: Acrididae, Tettigoniidae) from Türkiye and Iran, and a key to species of Abalakeus is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The subfamily Erythraeinae Robineau-Desvoidy includes 27 genera (Noei et al 2017;Saboori et al 2023), of which five genera have been reported in China (Xu et al 2022b). Hitherto, the genus Erythraeus Latreille, 1806 was reported worldwide except for Antarctica and comprises three subgenera (Mąkol & Wohltmann 2012;Roland & Gabryś 2020;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subfamily Erythraeinae Robineau-Desvoidy includes 27 genera (Noei et al 2017;Saboori et al 2023), of which five genera have been reported in China (Xu et al 2022b). Hitherto, the genus Erythraeus Latreille, 1806 was reported worldwide except for Antarctica and comprises three subgenera (Mąkol & Wohltmann 2012;Roland & Gabryś 2020;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The subfamily Erythraeinae Robineau-Desvoidy includes 27 genera (Noei et al . 2017; Saboori et al . 2023), of which five genera have been reported in China (Xu et al .…”
Section: Introductionmentioning
confidence: 99%